1980
DOI: 10.1104/pp.66.2.330
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Role of Zein and Glutelin as N Sinks in Maize

Abstract: Zea mays grown with high levels of N fertilizer transports more sucrose into kernels than with low N. Sucrose translocation was greatest in genotypes with the highest capacity to deposit nitrogenous compounds as zein and glutelin in the kernel. These two proteins combined contain about 80% of the total N in the kernel and about 60% of the total N in the plant at maturity. They appear to serve as a functional N sink for the deposition of nitrogenous compounds. As the N sink capacity increases with additional av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 18 publications
(15 reference statements)
1
28
0
Order By: Relevance
“…5) were also similar to compositional modifications produced in kernels of plants from N fertility experiments (19,20,26). The greatest response to N supply occurred with zein, while relative increases in albumin/globulin and glutelin fractions were significant, but smaller (Fig.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…5) were also similar to compositional modifications produced in kernels of plants from N fertility experiments (19,20,26). The greatest response to N supply occurred with zein, while relative increases in albumin/globulin and glutelin fractions were significant, but smaller (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…This independence does not preclude a coupled regulation between starch and protein formation when N limits starch synthesis, but it does suggest that such regulatory mechanisms may not exist. For example, in this study starch and zein synthesis responded differently to alleviation of N stress, as indicated by the fact that zein is the primary N component of the endosperm (26) and the N use efficiency of starch production declined with increased N content of the endosperm (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, translocation ofC and N have been often considered independently (11,13), even though metabolism of C and N are closely linked (3). Sucrose transfer from vegetative parts to the ear is linked to zein accumulation in maize kernels (21). All these data have been obtained from net variation in C and N content of the various organs.…”
Section: Materials and Methods Plant Culture And Labeling Experimentsmentioning
confidence: 99%